Long noncoding RNAs in acute myeloid leukemia: biomarkers, prognostic indicators, and treatment potential - Maryam Farajzadeh; Mehrdad Fathi; Pooya Jalali; Armin Mahmoudsalehi Kheshti; Shahla Khodayari; Mohammad Hojjat-Farsangi; Farhad Jadidi (Cancer Cell International)
Abstract Long noncoding RNAs (lncRNAs) have been recognized as significant modulators of gene expression and are essential for various biological functions, even though they don’t appear to have the ability to encode proteins. Originally considered dark matter, lncRNAs have been recognized as being dysregulated and contributing to the onset, progression, and resistance to treatment of acute myeloid leukemia (AML). AML is a prevalent type of leukemia characterized by the disruption of myeloid cell differentiation, leading to an increased number of immature myeloid progenitor cells. Currently, the need for novel biomarkers and treatment targets to enhance therapeutic alternatives has led to a focus on lncRNAs as possible indicators for prognostic, therapeutic, and diagnostic systems in various human cancers, including AML. Recent research has recognized a limited set of lncRNAs as possible prognostic biomarkers or diagnoses in AML. This review evaluates the key research that highlights the significance of lncRNAs in AML and discusses their roles and impacts on the disease. Furthermore, we intend to underscore the importance of lncRNAs as new and trustworthy markers for the diagnosis, prediction, drug resistance, and targets for treatment in AML.